Effect of hot pressing on the microstructure and thermoelectric properties of TGZM-grown YbFe-doped CoSb3 skutterudite. Issue 7 (1st April 2021) - Li, Xuguang; Li, Shuangming; Li, Dou; Yang, Bin; Xu, Changjiang; Zhong, Hong
Abstract: Skutterudites based on CoSb3 are considered potential candidates in thermoelectric applications in the field of mid-temperature power generation. The annealing process necessitates more than a week to complete the peritectic phase transition for traditional melting-quenching-annealing-sintering methods. Herein, a new strategy combining the temperature gradient zone melting process with hot pressing (TGZM-HP) was successfully employed to synthesize YbFe-doped p-type CoSb3 in a shorter time. The resulting samples show enhanced thermoelectric properties compared to TGZM-grown ones, especially in the case of 1 at.% YbFe-doped CoSb3 . This compound exhibits a maximal Seebeck coefficient of 166.3 μVK −1 and a power factor of 1.8 mWm −1 K −2  at 723 K, showing an increase in these values of 25% and 51%, respectively. Moreover, phonon scattering appears to be enhanced due to the significant reduction in the grain size of the TGZM-HP samples, resulting in a minimum thermal conductivity of 2.71 Wm −1 K −1 . A dimensionless figure of merit ( ZT ) of 0.48 was obtained for 1 at.% YbFe-doped CoSb3 . This value is 1.6 times larger than that measured for TGZM-grown CoSb3 . This work provides an alternative strategy to fabricate skutterudite materials and foster their development.